Evolution and Tensions in the Formation of an Information Infrastructure: Case Study of the Integrated Management System of the Federal University of Rio Grande do Norte - da Silva, Larrissa Dantas; Motta, Gustavo Henrique Matos Bezerra (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2021)
The objective of this research is to study, from the theoretical perspective of information infrastructures (II), the evolution and sociotechnical tensions in the formation of the Integrated Management System (IMS) of the Federal University of Rio Grande do Norte, which is widely used in public higher education institutions in Brazil. The research is based on an exploratory qualitative strategy, using the case study as a method. The methods for data collection were three: collection of documents, interviews and questionnaires. For the stage of selection, analysis and interpretation of the data, a framework was developed that was based on the theoretical foundations of the II and its objective is to systematize the analysis of the results. As a result of this research, it is possible to identify the process of how the evolution and tensions suffered by the IMS occurred and occurs, as well as an analysis framework that can be used in the continuation of this work and for the scientific community.